SINQWAIN METHOD IN TEACHING RUSSIAN LANGUAGE - Sharipova Dilbar Gulamovna (Journals Park Publishing, 2023)
The article provides data on the translation of the Russian language in the areas of agronomy. To improve the conduct of classes and the development of oral speech, use a new pedagogical methodology, SINQWINE technology.
Keywords: Sinkwine, methodology, technology, formation, communication, reflection.